Membangun Keterampilan Motorik Kasar Anak Usia Dini Melalui Olahraga - Zulia Syiva Salsabila; Rivan Saghita Pratama (Institut Nalanda, 2025)
The development of gross motor skills in early childhood is a crucial component of their growth and development. However, the implementation of sports programs that support these skills often faces challenges, including inadequate facilities and a lack of understanding among educators and parents regarding the importance of gross motor skills. Effective solutions to overcome these challenges involve providing facilities that support children's physical activities, increasing educators' and parents' knowledge of the significance of gross motor skills, and implementing playful and creative learning methods. Additionally, traditional games can serve as an effective alternative in the development of children's gross motor skills. A comprehensive approach, including specialized training for educators and enhanced parental involvement, is necessary to achieve optimal development in early childhood.